Relaxin-2 Does Not Ameliorate Nephropathy in an Experimental Model of Type-1 Diabetes - Thomas Bernd Dschietzig; Katharina Krause-Relle; Maud Hennequin; Karoline von Websky; Jan Rahnenführer; Jana Ruppert; Hans Jürgen Grön; Franz Paul Armbruster; Ross A. D. Bathgate; Joerg R. Aschenbach; Wolf-Georg Forssmann; Berthold Hocher (Karger Publishers, 2015)
Background/Aims: In diabetic nephropathy (DN), the current angiotensin-II-blocking pharmacotherapy is frequently failing. For diabetic cardiomyopathy (DC), there is no specific remedy available. Relaxin-2 (Rlx) - an anti-fibrotic, anti-inflammatory, and vasoprotecting peptide - is a candidate drug for both. Methods: Low-dose (32 µg/kg/day) and high-dose (320 µg/kg/day) Rlx were tested against vehicle (n = 20 each) and non-diabetic controls (n = 14) for 12 weeks in a model of type-1 diabetes induced in endothelial nitric oxide synthase knock-out (eNOS-KO) mice by intraperitoneal injection of streptozotocin. Results: Diabetic animals showed normal plasma creatinine, markedly increased albuminuria and urinary malonyldialdehyde, elevated relative kidney weight, glomerulosclerosis, and increased glomerular size, but no relevant interstitial fibrosis. Neither dose of Rlx affected these changes although the drug was active and targeted plasma levels were achieved. Of note, we found no activation of the renal TGF-β pathway in this model. In the hearts of diabetic animals, no fibrotic alterations indicative of DC could be determined which precluded testing of the initial hypothesis. Conclusions: We investigated a model showing early DN without overt tubulo-interstitial fibrosis and activation of the TGF-β-Smad-2/3 pathway. In this model, Rlx proved ineffective; however, the same may not apply to other models and types of diabetes.